Answer:
X = 1
Explanation:
To solve the system of equation by susbtitution:
3x + y = 9
y = –4x + 10
We can follow the steps thus:
Substitute the value of y in the first equation:
As in the second equation y = -4x + 10 we can substitute in the first equation as follows:
3x + y = 9
3x + -4x + 10 = 9
Combine like terms:
3x + -4x + 10 = 9
Like therms are the therms with X (3x - 4x = -1x):
-1x + 10 = 9
Apply the subtraction property of equality:
-1x + 10 = 9
As 10 is suming, it passes to subtracting the 9:
-1x = 9 - 10
-1x = -1
Apply the division property of equality:
-1x = -1
Dividing in -1:
x = -1 / -1
X = 1